Do Board Expertise and Networked Boards Affect Environmental Performance? - Homroy, Swarnodeep (Journal of business ethics, 2019)
We examine the resource provision role of the board of directors in ensuring substantive corporate sustainability practices. Specifically, we examine two channels of resource provision (i.e., the presence of non-executive directors with previous experience in environmental issues—EEDs—and network connections of EEDs) that can affect a firm’s ethical and environmental behavior. Using greenhouse gas (GHG) emissions data from FTSE 350 firms, as a measure of environmental performance, we show that the presence of EEDs on the board is associated with lower GHG emissions. Further, firms with better-networked EEDs have better environmental performance. A possible mechanism is that firms with EEDs invest more in environmental technology. These results suggest that, in addition to the traditional role of shareholder value maximization, the board of directors also caters to the interests of wider stakeholders of the firm by facilitating substantive ethical practices.